Simplified Detection System for Neuroreceptor Studies in the Human Brain - Bice, Alden N; Wagner, Henry N., Jr; Frost, J. James; Natarajan, T. K; Lee, Myung C; Wong, Dean F; Dannals, Robert F; Ravert, Hayden T; Wilson, Alan A; Links, Jonathan M (The Journal of nuclear medicine (1978), 1986)
A simple, inexpensive dual-detector system has been developed for measurement of positronemitting receptor-binding drugs in the human brain. This high efficiency coincidence counting system requires that only a few hundred microcuries of labeled drug be administered to the subject, thereby allowing for multiple studies without an excessive radiation dose. Measurement of the binding of [11C]carfentanil, a high affinity synthetic opiate, to opiate receptors in the presence and in the absence of a competitive opiate antagonist indicates the potential utility of this system for estimating different degrees of receptor occupation in the human brain.